Production of sustainable methane from renewable energy and captured carbon dioxide with the use of Solid Oxide Electrolyzer: A thermodynamic assessment. (15th March 2015) - Stempien, Jan Pawel; Ni, Meng; Sun, Qiang; Chan, Siew Hwa
Abstract: A possible pathway for renewable and sustainable methane production from captured carbon dioxide, water (or seawater) and renewable electricity is proposed and analysed. The proposed system includes Solid Oxide Electrolyzer Cell combined with ex-situ methane synthesis reactor comprising Sabatier, Methanation and Water-Gas Shift reactions. A well validated electrochemical model is used to describe the behaviour of the electrolyzer for steam/carbon dioxide co-electrolysis. The methane synthesis reactor is modelled by a set of equations based on thermodynamic equilibrium reaction constants. Effects of current density, temperature, pressure and initial steam to carbon dioxide ratio on system performance are analysed and their effects are discussed. It is found that a simple, single-pass system without heat recuperation could achieve a maximum overall energy efficiency of 60.87% (based on lower heating value), a maximum electrical energy efficiency of 81.08% (based on lower heating value), and a maximum amount of methane production of ∼1.52 Nm 3 h −1 m −2 of electrolyzer. It is also found that conversion of ∼100% captured carbon dioxide is possible in the proposed system. Highlights: Analysis of Solid Oxide Electrolyzer combined with methane synthesis process. Efficiency of converting water and carbon dioxide into synthetic, renewable methane above 81%. Effects of process temperature, pressure, gas flux and compositions were analysed. Methane production of ∼1.52 [Nm 3 h −1 m −2 of electrolyzer]. Conversion of ∼100% of captured CO2 is possible.